Investigação do Ângulo de Fase como preditor da resposta virológica em pacientes portadores de hepatite C - Dorna, Mariana de Souza [UNESP] (2016)
Background. Hepatitis C virus is one of the major causes of liver chirrosis and hepatocellular carcinoma. The objective of the treatment with Pegylated Interferon and Ribavirin was to achieve the cure of the virus. So far, we have no gold-standard methodology to assess the body composition of these patients. The aim of our study was to evaluate the association of baseline Phase Angle (PhA), and it’s variation, with virological response treatment week 24 with Pegylated Interferon and Ribavirin and sustained virological response. Methods. Patients were prospectively evaluated for 6 months, from April 2010 to June 2013. A tetrapolar single-frequency bioimpedance were performed at baseline and at treatment week 24. Biochemical and liver biopsy data were collected from the patient´s medical chart. Results. A total of 87 patients with mean age of 49.78 ± 10.51 y were studied ,47.12% were male. The phase angle mean was 6.56 ± 0.78°.A total of 49 (56.32%) of them achieved virological response at treatement week 24 and 43 (49.4%) reached sustained virological response. Considering the genotype- 1 population 51% achieved virological response at tw 24, 46% SVR and 54% were non-responders. Among the population studied, 38.88% of näive genotype-1 patients achieved sustained virological response, 36.84% of previous NR achieved sustained virological resposnse. Regarding non gentotype-1 population 57.14% achieved SVR and among them 70% were naive. Considering sustained virological response, baseline Phase Angle values showed no statistical difference between the groups (p>0.05).Regarding virological response at treatment week 24, Phase Angle values showed no statistical difference between the groups Phase angle was not associated with virological response at treatment week 24 (OR:1.423; CI95%: 0.328-6.172; p: 0.637). The variation of phase angle during the 24 weeks of treatment was associated with virological response at 24 week (OR:1.099; CI95%:1.027-1.176; p:0.006). Conclusion. Our findings suggest that PhA was not associated neither with virological response at treatment week 24 to sustained virological response. However, its variation (delta) within 24 weeks of treatment was associated with virological response at tw24.